Old Petersburg and the Broad River Valley of Georgia Their Rise and Decline - Coulter, E. Merton (Georgia Open History Library, 1965)
Old Petersburg and the Broad River Valley of Georgia details colonial life at Petersburg, Georgia, at the junction of Broad and Savannah Rivers. A town that grew, flourished, and eventually disappeared, Petersburg was once a valuable and unique outlet for river trade. This volume highlights various aspects of this river town, including its founding, politics, businesses, and religious practices. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.